2018
DOI: 10.15344/2456-3501/2018/137
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of High Pulse Pressure and Renal Function in Patients with Chronic Kidney Disease: Analysis for each Stage of Chronic Kidney Disease

Abstract: In the present study, we retrospectively investigated consecutive patients who visited the Nephrology Medicine Department of Yokosuka Kyousai Hospital between September 2006 and October 2011. In total, our study included 104 participants with CKD (stage G3a-G5) who were diagnosed with hyperlipidemia and commenced on high potency statins. The average normal PP is 50 mmHg, and the risk of CVD increases when PP is ≥65 mmHg [11]. The participants were categorized on the basis of their PP: ≥65 mmHg was the High PP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Meanwhile, pulse pressure is closely related to SBP and DBP [4] and increases gradually with age [5,6] . Previous studies have demonstrated an association of PP with several adverse outcomes such as type 2 diabetes mellitus (T2DM) [7] , metabolic syndrome [8] , cardiovascular events [9] [10] [11] , stroke [12] , chronic kidney disease [13] and even death [14, 15] [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, pulse pressure is closely related to SBP and DBP [4] and increases gradually with age [5,6] . Previous studies have demonstrated an association of PP with several adverse outcomes such as type 2 diabetes mellitus (T2DM) [7] , metabolic syndrome [8] , cardiovascular events [9] [10] [11] , stroke [12] , chronic kidney disease [13] and even death [14, 15] [16] .…”
Section: Introductionmentioning
confidence: 99%